Antropogênese do relevo por mineração: uma abordagem voltada para o diagnóstico de seus efeitos a partir do estudo de Itaoca (ES) - Frechiani, Juliana Mendes (2021)
This research aimed to investigate and compare the morphological changes in the landscape caused by anthropic interference. The district of Itaoca, city of Cachoeiro de Itapemirim, in the state of Espírito Santo/Brazil was chosen because its morphology and impact by the extraction and processing of stone (quarrying) in order to atend the demands of the international market. The research is based on the application of retrospective geomorphological mapping for the proof of landscape transformations, such as changes in hydrography and the shaping of anthropogenic lagoons for the period 1970s to 2012/15. For this analysis, we considered the changes in land use and land cover in the years 1970, 2007/08, 2012/15 and 2019, pointing out the relations of economic activities, mainly exploration and processing of stones, and how it changed the morphology. The changes in the hydrography were described by morphometric parameters in order to correlate the implications of human actions on the natural processes, to prove and also to dimension the changes on the physical environment. In the first moment, a bibliographic and cartographic survey were carried out. Subsequently, photointerpretation analyses were conducted and geomorphological mapping based on the proposals of Tricart (1965), Verstappen and Zuidam (1975), Simon (2007), Valeriano (2008) adaptations of Dikau (1990), Florenzano (2008) adaptations of Dent and Young (1981) Paschoal, Conceição and Cunha (2010), Valeriano and Albuquerque (2010) and Paschoal (2011, 2014). As a result, there was observed an expansion of the mining class between 1970s and 2012/15 in the northeastern side. There was a direct impact on the relief that promoted the development of anthropogenic morphology, such as the expansion of anthropogenic lagoons. In terms of main river length, total stream length and drainage density, the stream channels have been reduced. In addition, the decrease in the hierarchical orders of streams were observed from 1970 to 2012/15 over a fifty-year interval. The geomorphological mapping on the scale 1:10,000 showed that the human actions on the morphology were decisive for shaping new flow patterns, directly influencing the depositions in the plain area alluvial accumulation. The excavations resulted in the disfiguration of rounded interfluves and created rectilinear surfaces, causing the predominance of concave and rectilinear planar slope forms. In this way, it was possible to verify the human being as a geomorphological agent, and the geomorphological cartography as an important instrument in the supply of information, subsidizing the planning of human actions that are developed on the physical environment.